2013
DOI: 10.1002/asia.201300365
|View full text |Cite
|
Sign up to set email alerts
|

Seed‐Assisted, One‐Pot Synthesis of Hollow Zeolite Beta without Using Organic Structure‐Directing Agents

Abstract: Hollow aluminosilicate zeolite beta was successfully synthesized by adding CIT-6, that is, zincosilicate zeolite, which has the same topology as beta, as seeds to the Na-aluminosilicate gel without the need for organic structure-directing agents. One important factor in the successful organic structure-directing agent (OSDA)-free synthesis of hollow beta crystals is the solubility of the seed crystals in alkaline media. CIT-6 was less stable than aluminosilicate zeolite beta in alkaline media and the solubilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 37 publications
3
36
0
1
Order By: Relevance
“…The “hollowing” zeolite process has been widely reported for zeolites with MFI framework type, leading to nanoboxes with regular zeolitic walls whose thickness can be controlled down to a few nanometers . More recently, we succeeded in preparing hollow Beta and Y zeolite crystals, with *BEA and FAU framework types, respectively …”
Section: Methodsmentioning
confidence: 99%
“…The “hollowing” zeolite process has been widely reported for zeolites with MFI framework type, leading to nanoboxes with regular zeolitic walls whose thickness can be controlled down to a few nanometers . More recently, we succeeded in preparing hollow Beta and Y zeolite crystals, with *BEA and FAU framework types, respectively …”
Section: Methodsmentioning
confidence: 99%
“…However,am ajor drawback is that the use of OSDAs makes commercialization of zeolites extremely expensive and additionally requires complex processing stages, which strictly limits the industrial use of OSDA-directed zeolites. [8][9][10] Furthermore, severalz eolitest hat required the use of an OSDA, such as RUB-13, [11] ZSM-12, [12][13][14] ZSM-11, [10] ECR-18, [10] ZK-20, [15] hollow-beta, [16] omega, [17] MCM-68, [18] VPI-8, [19] ZSM-22 [20] and NU-87, [21] were successfully synthesized by the seed-assisted method without the use of any OSDAs. For instance, the conventionals ynthesis of zeoliteb etarequired the use of OSDA until Xie et al [7] reported the first OSDA-free synthesis in which zeolite betas eeds were added to an aluminosilicate reactantg el in the absence of OSDA.…”
Section: Introductionmentioning
confidence: 99%
“…One important factor in the successful organic structure directing agent (OSDA)-free synthesis of hollow beta crystals is the solubility of the seed crystals in alkaline media. 63 CIT-6 was less stable than aluminosilicate zeolite beta in alkaline media and the solubility changed depending on whether the crystals were calcined or not. Figure 6 shows the TEM image of the sliced crystal.…”
Section: Template-free Strategymentioning
confidence: 97%
“…The crystal growth proceeded from the outside inward after the complete dissolution of the CIT-6 seed crystal. 63 …”
Section: Template-free Strategymentioning
confidence: 97%